x^{2}y - 16y + 32 - 2x^{2} what i came up with so far is y(x^{2} - 16) + 32 - 2x^{2} y(x + 4)(x - 4) + 32 - 2x^{2 }
Follow Math Help Forum on Facebook and Google+
Originally Posted by PaperStSoap x^{2}y - 16y + 32 - 2x^{2} what i came up with so far is y(x^{2} - 16) + 32 - 2x^{2} y(x + 4)(x - 4) + 32 - 2x^{2 }
32 + 2x^2 = -2(-16 + x^2) = -2(x^2 - 16) = -2(x + 4)(x - 4) (y-2)(x+4)(x-4) is this right?
Originally Posted by PaperStSoap 32 + 2x^2 = -2(-16 + x^2) = -2(x^2 - 16) = -2(x + 4)(x - 4) (y-2)(x+4)(x-4) is this right? Didn't you read the post directly above this one?
i was actually typing that response before yours came up.
View Tag Cloud